APPLICATION OF BINOMIAL DISTRIBUTION IN LOGISTICS SYSTEMS: APPLICATION OF BINOMIAL DISTRIBUTION IN LOGISTICS SYSTEMS - Kalev, Krasimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A downtime interval during which a machine is performing no work due to lack of a spare part is an important economical issue for companies. It has to know in advance the need for spare elements to ensure reliable operation of the machines. In order to determine the required amount of spare elements used a scientific approach. In this paper is proposed a well-known statistical approach to inventory management. The binomial distribution permits to analyze without difficulties the operational reliability and calculating the spare parts demand. Some of results are given by engineering software.